Prevalence of Albuminuria and Associated Factors among Gout Arthritis Patients in Cipto Mangunkusumo Hospital - Mahardhika, Jeffrey Christian; Anggoro, R.M. Suryo (Indonesian Rheumatology Association, 2018)
Background Gout arthritis associates with many comorbodities such as hyperuricemia, hypertension, hyperglycemia, obesity, and dyslipidemia, which are also factors for the development of/or predisposition factors of chronic kidney diseases (CKD). Albuminuria is a predictor factors for CKD. Screening for albuminuria is needed to be done in patients with high risk of CKD. This research was conducted to examine the prevalence of albuminuria and the associated factors in gout arthritis patients.Methods This research was a cross-sectional study from gout arthritis patientsâ medical records in Cipto Mangunkusumo Hospital. We included all gout patients who treated within 2011â2015. Subjects with chronic kidney disease, in kidney replacement therapy, hypertension â¥ 10 years, and diabetes â¥ 5 years were excluded. Albuminuria was determined by urine dipstick result of protein â¥ 1+. Factors associated were age, sex, hyperuricemia, hypertension, stage of hypertension, hyperglycemia, obesity, dyslipidemia, uric acid level, and body mass index (BMI). Data associated with the factors were recorded and the associations were tested with chi square, fisherâs exact, or independent t-test.Results from 54 subjects included in this research, the prevalence of albuminuria was 20.4%. There were no significant associations between all factors and albuminuria tested by chi square and fisherâs exact test. Independent t-testâs results also showed no significant associations between all the factors and albuminuriaConclusion The prevalence of albuminuria in gout arthritis patient was 20.4%. There were no significant associatons between age, sex, hyperuricemia, hypertension, hyperglycemia, obesity, dyslipidemia, uric acid level, and body mass index (BMI) tested with albuminuria in gout arthritis patients in Cipto Mangunkusumo Hospital from 2011â2015.Keywords: Prevalence, Albuminuria, Gout Arthritis, Risk Factors